2022
DOI: 10.3892/ol.2022.13355
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‑α and its effects on cancer cell apoptosis (Review)

Abstract: Interferon (IFN)-α is a cytokine that exhibits a wide range of biological activities and is used in various cancer treatments. It regulates numerous genes that serve roles in antiviral, antiproliferative and proapoptotic activities. For decades, one of the main aspects of clinical oncology has been the development of anticancer therapeutics that promote the effective elimination of cancer cells via apoptosis. However, the updated available information concerning IFN-α-induced cancer cell apoptosis needs to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…In cancer cells in general and in MCC cells in particular, type I IFNs can both inhibit their proliferation and induce apoptosis (Willmes et al 2012;Kotredes and Gamero 2013;Shi et al 2022). In line with these reports, treatment of MCPyV-positive WaGa and MKL-1, as well as MCPyVnegative UM-MCC34 MCC cell lines with recombinant IFNα 2a resulted in a dose-dependent inhibition of cell proliferation (Fig.…”
Section: Ifnα Inhibits MCC Cell Proliferation and Induces Apoptosissupporting
confidence: 76%
“…In cancer cells in general and in MCC cells in particular, type I IFNs can both inhibit their proliferation and induce apoptosis (Willmes et al 2012;Kotredes and Gamero 2013;Shi et al 2022). In line with these reports, treatment of MCPyV-positive WaGa and MKL-1, as well as MCPyVnegative UM-MCC34 MCC cell lines with recombinant IFNα 2a resulted in a dose-dependent inhibition of cell proliferation (Fig.…”
Section: Ifnα Inhibits MCC Cell Proliferation and Induces Apoptosissupporting
confidence: 76%
“…As well, the doubling time for KPC-Luc A and KPC-Luc-4580 cells also corresponded to their levels of resistance to VSV-ΔM51-GFP. It is understood that cancer cells typically downregulate antiviral signaling as these pathways are antiproliferative and pro-apoptotic ( 13 ). Also, in our previous studies, we demonstrated that cells in the G 2 /M cell cycle phase are transcriptionally repressed, leading to a decreased ability of cells to mount antiviral responses ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pantropism exhibited by VSV is largely due to its use of ubiquitously expressed receptors for attachment and entry into host cells, such as the low-density lipoprotein receptor ( 9 ). The oncoselectivity of most OVs, including VSV, is mainly due to defective or suppressed type I interferon (IFN)-mediated antiviral responses in many cancers ( 10 12 ), because most type I IFN responses are antiproliferative, antiangiogenic, and proapoptotic ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Type I IFN has powerful antitumor and antiviral effects (36). Among them, IFN-α can induce tumor cell apoptosis through the Fas-Fas pathway and plays an important role in tumor immunotherapy (37). IFN-γ is highly expressed in HL tissue cells and tumor HRS cells and has a potential impact on the prognosis of patients (38).…”
Section: Ifnmentioning
confidence: 99%